Effects of black locust (Robinia pseudoacacia) on soil properties in the loessial gully region of the Loess Plateau, China - Qiu, Liping; Zhang, Xingchang; Cheng, Jimin; Yin, Xianqiang (Plant and soil, 2010)
Black locust (Robinia pseudoacacia) has been widely planted in the Loess Plateau for soil and water conservation. The effects of black locust on soil properties has significant role in land use and ecosystem management. However, this beneficial effect has been little studied in the Loess Plateau. The soil properties below black locust and native grass growing in Nanxiaohe and Wangdonggou watersheds, located in the loessial gully region of the Loess Plateau, were studied for changes in soil properties after establishment of black locust. The black locust significantly increased soil cation exchange capacity, organic carbon, total nitrogen, nitrate, and carbon:nitrogen and carbon:phosphorus (P) ratios, as well as some enzymes like alkaline phosphatase and invertase in 0-20 cm or 0-80 cm depths of soil compared to the native grassland in Nanxiaohe and Wangdonggou watersheds. However, the effects on ammonium, total P, and extractable P and potassium were not consistent in both watersheds. There were more obvious differences in soil properties between black locust land and grassland for Nanxiaohe watershed than for Wangdonggou watershed, suggesting that the effects of black locust on most soil properties increase with black locust age. The results indicate that black locust has potential to improve soil properties in the loessial gully region of the Loess Plateau and the improvements were greater in long-term than middle-term black locust stands.